Lamin A/C gene: sex-determined expression of mutations in Dunnigan-type familial partial lipodystrophy and absence of coding mutations in congenital and acquired generalized lipoatrophy - Vigouroux, C; Magré, J; Vantyghem, M C; Bourut, C; Lascols, O; Shackleton, S; Lloyd, D J; Guerci, B; Padova, G; Valensi, P; Grimaldi, A; Piquemal, R; et al. (Diabetes (New York, N.Y.), 2000)
Lamin A/C gene: sex-determined expression of mutations in Dunnigan-type familial partial lipodystrophy and absence of coding mutations in congenital and acquired generalized lipoatrophy. C Vigouroux , J Magré , M C Vantyghem , C Bourut , O Lascols , S Shackleton , D J Lloyd , B Guerci , G Padova , P Valensi , A Grimaldi , R Piquemal , P Touraine , R C Trembath and J Capeau INSERM U402, Faculté de Médecine Saint-Antoine, Fédération de Biochimie, Hôpital Saint-Antoine, Paris, France. Abstract Missense mutations of the lamin A/C gene, LMNA, have been recently identified in Dunnigan-type familial partial lipodystrophy (FPLD), which belongs to a heterogeneous group of rare disorders affecting adipose tissue distribution and metabolism. In this study, we sequenced the LMNA coding region from patients presenting with FPLD or other forms of lipodystrophy. We identified two heterozygous mutations in exon 8, R482W and R482Q, in FPLD patients (six families and one individual) with various clinical presentations. In addition, we found a novel heterozygous mutation (R584H) in exon 11, encoding specifically the lamin A isoform, in a patient with typical FPLD. Clinical and biochemical investigations in FPLD patients revealed that the expression and the severity of the phenotype were markedly dependent on sex, with female patients being more markedly affected. In subjects with generalized lipoatrophy, either congenital (13 case subjects) or acquired (14 case subjects), or Barraquer-Simon syndrome (2 case subjects), the entire LMNA coding sequence was normal. Although FPLD mutations are predominantly localized in exon 8 of LMNA, the finding of a novel mutation at codon 584, together with the R582H heterozygous substitution recently described, confirms that the C-terminal region specific to the lamin A isoform is a second susceptibility region for mutations in FPLD.